Recycling of waste or crude lubricating oil by vacuum distillation to produce reusable lubricants and its economic viability evaluation (Journal of Bangladesh Academy of Sciences, 2022)
Recycling waste or crude lubricant oil is the best alternative to incineration. This article used the vacuum distillation method to recycle of waste lubricant oil. About 90% of lubricating oil was recovered from waste oil within the temperature range of 60-360 0C. Every measured property like density, viscosity, flash point, pour point, sulfur content, carbon residue, ash content, and water content were investigated and compared with fresh oil. Pour point was found not to improve through vacuum distillation but rather decreased. Similarly, vacuum distillation could not improve the viscosity and density of recycled material but rather decreased. Adding 2% EPDM, SPO ESPRENE V0141, and pellet form of rubber as additives increased those two properties significantly. Finally, 0.1% NaNO3 was also added as an antioxidant. So, lastly, it can be concluded that the vacuum distillation process can effectively recycle waste lubricant oil in an economical and environmentally friendly manner.J. Bangladesh Acad. Sci. 46(1); 19-29: June 2022